Investigation of the knowledge levels of nurses and midwives about autism and its early diagnosis - Emine Geckil; Emine Geçkil (Asian Pacific Journal of Health Sciences, 2016)
Objective: The aim of this study is to examine the knowledge levels of nurses and midwives working in the field of children’s health about autism and its early diagnosis. Materials and Methods: This descriptive study has been carried out with 248 nurses and midwives working with children in Gaziantep, Turkey. Data were collected with a questionnaire consisting of 30 questions and it was analyzed by the frequency, mean, t-test and Anova. Results: It has been determined that 55.2% of participants were nurse, and 66.1% of them did not read to literature about autism. It has been determined that the participants’ knowledge scores about the autism and its early diagnosis is in moderate level. The ones having graduate and undergraduate degree have higher knowledge and the ones working for more than 11 years and who are older than 33 years old have lower knowledge scores. Conclusions: The results of this study have indicated that all nurses/midwives providing service for children should be informed and the nurses/ midwives with low knowledge level should be given priority.